Attitudes of health professionals towards people with substance use disorders in Brazil, controlling for the effects of social desirability. (10th February 2022) - Leite Ferreira, Vitor; Gonçalves de Andrade Tostes, Joanna; Knaak, Stephanie; Silveira, Pollyanna Santos da; Fernandes Martins, Leonardo; Mota Ronzani, Telmo
Abstract: Health professionals are in a strategic position to help people with substance use disorders (SUDs) who seek health services for support or treatment. However, it is known that professionals' attitudes towards people who use alcohol and other drugs are marked by stigmatizing attitudes that create barriers to access quality treatment and make it difficult for the user to adhere to it. From this, the present study aimed to investigate the attitudes of 264 health professionals from specialised services and primary health care (PHC) in the Southeast region of Brazil, through Opening Minds Scale for Healthcare Providers (OMS‐HC), taking into account the hypothesis of contact with the subject as a predictor of more positive attitudes. For this, a Multiple Hierarchical Regression was carried out to ascertain the contribution of the variables used in the explanatory model of attitudes. In addition, the measure of social desirability ( SD ), assessed by Brazilian Portuguese adaptation of Marlowe–Crowne Social Desirability Scale, was used as a control variable in the regression model to obtain a more robust and accurate model regarding the presence of biased responses, pervasive in studies on attitudes. In general, our findings showed that contact/familiarity with substance use, either through direct contact with users or through the respondent's own use, predicted more positive attitudes, with specialised service professionals expressing more positive attitudes than those working in PHC. Blaming the user for his/her condition presented itself as a predictor of more negative attitudes. Studies like this are of paramount importance for understanding the relationship established between professionals and service users and, therefore, for tailoring interventions and programs that aim to reduce stigmatizing attitudes and provide better access to health for people with SUDs. The importance of using the SD measure as a control variable in Regression is also emphasised, as an effective way to overcome to a common limitation in studies of attitudes.